A Study to Assess the Effectiveness of a Structured Teaching Plan on Knowledge Regarding Premenstrual Symptoms Among Early Adolescent Girls in Selected Schools of Agra - Tanuja Singh; Manisha Gond; Himanshi Kukreti; Deepanjali Bagla; Ankita Maurya; Rakesh Kumar Yadav; Seema Yadav (International Journal of Midwifery Nursing And Practices, 2026)
Premenstrual symptoms are commonly experienced by many women and can have a considerable impact on their everyday functioning and overall well-being. These symptoms involve physical, emotional, and behavioral changes that occur during the luteal phase of the menstrual cycle, with different levels of severity. The present study was conducted to evaluate the effectiveness of a structured teaching plan on knowledge regarding premenstrual symptoms among early adolescent girls in selected schools of Agra. The study aimed to assess knowledge levels before and after the intervention, determine the effectiveness of the teaching programme, and examine the relationship between pretest knowledge scores and selected demographic factors. The study was carried out at St. Vincent’s Girls Higher Secondary School, Agra, using a sample of 40 early adolescent girls selected from the accessible population. The findings showed that in the pretest, 15% of participants had poor knowledge, 77.5% had average knowledge, and 7.5% had good knowledge. Following the structured teaching plan, improvement was observed in the posttest, where 7.5% had poor knowledge, 70% had average knowledge, and 22.5% had good knowledge. The posttest mean knowledge score was higher than the pretest score, indicating the effectiveness of the intervention. Statistical analysis using the chi-square test revealed a significant association between awareness of premenstrual symptoms and pretest knowledge scores, whereas other demographic variables did not show any significant association. Overall, the study concluded that the structured teaching plan was effective in enhancing knowledge regarding premenstrual symptoms among early adolescent girl.
Keywords: Adolescent girls; Knowledge; Premenstrual symptoms; health education; structured teaching plan